Narrativas orais do povo indígena Tapuia do Carretão - Rodrigues, Eunice da Rocha Moraes (2020)
The Tapuia Oral Narratives, an Indigenous People from Carretão, is an authorial work that aims to highlight and record the oral narratives transmitted by the elders man and elders woman of the village over time, from the first settlement in the imperial age to the present time. In this work, the entire struggle of a people, their victories and their defeats are evidenced in the timeline, but, above all, the willingness day by day to guarantee the defense and the possession of the territory against invaders who always had affronted and have affronting the life. This dissertation is composed of four special components, The Panorama, The Context, The Scenery and The Performances. Panorama briefly records some considerations from Cabral's arrival to the present day. In the Context covers the formation of the Tapuia people in Goiás, the foundation of the Imperial Village, location data and characteristics of the constitution of the indigenous peoples of the region. The Scenery show life in the community and the daily life of mine as author of the work. At last, Performances, where there are oral narratives collected during the elaboration of the work, in which the way of relating the playful with the magician and the supernatural is evidenced, as a way of holding the attention of children and, even adults who they heard from their mothers and grandmothers the incredible local stories and legends, which never ended with "and they lived happily ever after", but "and they still live today".